Kinematics to Understand How Clinical Diagnoses Translate into Manual Daily Life. Performance in Persons with Stroke and Multiple Sclerosis - Hermsdörfer, Joachim; Vojta, Heike; Schmidle, Stephanie; Rieckmann, Peter; Gulde, Philipp (Springer Science and Business Media Deutschland GmbH, 2024)
Several tests of sensorimotor control of the upper extremity are in use to assess the consequences of neurological diseases. It is however unclear how informative these tests are to predict patient’s performance in daily life. We therefore compared lab-based tests with objective assessments of spontaneous hand movement in daily life. Patients with stroke and multiple sclerosis as well as control subjects wore smart watches on both wrists and movement kinematics were derived from accelerometers and gyroscopes. While asymmetries in the performances of the hands in patients was quite stable across tasks and measurement approaches, predictions of the magnitude of deficits in daily life were possible but associated with large variability. Kinematic analyses add information on daily life performance, which is not available from clinical tests and enables longitudinal monitoring of disease progression and recovery.
CRIS-Team Scopus Importer:2025-02-04